1998
DOI: 10.1017/s0950268897008480
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Toxoplasma gondii specific immunoglobulin G antibodies among pregnant women in Norway

Abstract: During one year from June 1992 serum IgG antibodies to Toxoplasma gondii among 35,940 pregnant women were measured in a cross-sectional study conducted in Norway. The overall prevalence was 10.9%. The lowest prevalences were detected in the north (6.7%) and in the inland counties (8.2%). A significantly higher prevalence was detected in the southern counties (13.4%) where a mild, coastal climate prevails. Women with foreign names had a higher prevalence (22.6%) than women with Norwegian names (10.0%). The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
3
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 24 publications
6
58
3
4
Order By: Relevance
“…Pregnant women who had more than two children were more exposed to toxoplasmosis in this study. Similar findings have been reported in several studies [5,22,23]. However, multiparity, which increases the prevalence of toxoplasmosis, is still unknown [5].…”
Section: Discussionsupporting
confidence: 89%
“…Pregnant women who had more than two children were more exposed to toxoplasmosis in this study. Similar findings have been reported in several studies [5,22,23]. However, multiparity, which increases the prevalence of toxoplasmosis, is still unknown [5].…”
Section: Discussionsupporting
confidence: 89%
“…20,27,31,32 This is the first of its kind, to our knowledge, reported in Thailand and the number of children that have contributed to the increasing Toxoplasma prevalence in women is unknown. Possible explanations for this problem are that women with children are more likely to have contact with plausible risk factors to Toxoplasma acquisition or they are careless when preparing food that can lead to contamination 32 or because their children have more contact with stray cats. Nevertheless, an earlier study stated that children have not been identified as an independent risk for prevalence of Toxoplasma .…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of previous toxoplasma infection in pregnant women ranges from 10% in the United Kingdom 10 and Norway 11 to around 55% in France 12 and Greece 13 ; in many countries it has declined sharply over the past three decades. [14][15][16] Regional variation has been attributed to climate, 11 cultural differences in the amount and type of raw meat consumed, 7 17 and the increased consumption of meat from animals farmed indoors and frozen meat.…”
Section: Introductionmentioning
confidence: 99%